Avaliação do uso e eficácia da Tecnologia da Informação no Sistema de Transporte Público - Varandas, Marcus Vinicius Delgado (2012)
The Public Transportation Systems provides modern technology able to improve operation performance , comfort and safety for the costumers. This work intends to study the uses of Information Technology, its application and results as subsidy for planning and management of public transportation of passangers, predominantly fulfilled by bus. The basic hypothesis of this work is that the technological resources available are not used or are used inadequately by the managers and operators of the public transportation. The work invastigates what is known by quality on public transportation in literature and how it is conceived by the agents envolved: costumers, operators, managers and the community in general. This works shows, still, the basic concepts of Intelligent Transportation Systems, and the details and analysis of applications on public transportation, in special those regarding resources in Information Technology. The details of a survey that aimed to identify which technological resources are used by the organ managers of public transportation, in many city in Brazil, and that should be able to turn in improvements of quality of the system, completed the work. The result of this survey indicated that, even though there is a range of technologies available, the use of this potential is very small, and contributes little for the improvements of quality of the public transportation.